A combined electrohydrodynamic atomization method for preparing nanofiber/microparticle hybrid medicines - Sun, Liang; Zhou, Jianfeng; Chen, Yaoning; Yu, Deng-Guang; Liu, Ping (Frontiers in Bioengineering and Biotechnology, 2023)
Bacterial prostatitis is a challenging condition to treat with traditional dosage forms. Physicians often prescribe a variety of dosage forms with different administration methods, which fail to provide an efficient and convenient mode of drug delivery. The aim of this work was to develop a new type of hybrid material incorporating both electrosprayed core-shell microparticles and electrospun nanofibers. A traditional Chinese medicine (Ningmitai, NMT) and a Western medicine (ciprofloxacin, CIP) were co-encapsulated within this material and were designed to be released in a separately controlled manner. Utilizing polyvinylpyrrolidone (PVP) as a hydrophilic filament-forming polymer and pH-sensitive Eudragit ® S100 (ES100) as the particulate polymeric matrix, a combined electrohydrodynamic atomization (EHDA) method comprising coaxial electrospraying and blending electrospinning, was used to create the hybrids in a single-step and straightforward manner. A series of characterization methods were conducted to analyze both the working process and its final products. Scanning electron microscopy and transmission electron microscopy revealed that the EHDA hybrids comprised of both CIP-PVP nanofibers and NMT-ES100 core-shell microparticles.Multiple methods confirmed the rapid release of CIP and the sustained release of NMT. The antibacterial experiments indicated that the hybrids exhibited a more potent antibacterial effect against Escherichia coli dh5α and Bacillus subtilis Wb800 than either the separate nanofibers or microparticles. The amalgamation of fibrous nanomedicine and particulate micromedicine can expand the horizon of new types of medicines. The integration of electrospinning and coaxial electrospraying provides a straightforward approach to fabrication. By combining hydrophilic soluble polymers and pH-sensitive polymers in the hybrids, we can ensure the separate sequential controlled release of CIP and NMT for a potential synergistic and convenient therapy for bacterial prostatitis.